Pengaruh Media Sosial Pada Promosi di Bagian Pemasaran ITB STIKOM BALI - Astiti, Ni Made; Ulandari, Ni Wayan Ari; Putra, I Putu Warma (UHN IGB Sugriwa Denpasar, 2024)
Digital marketing, or digital marketing, is an effort or method to promote a brand or product using digital-based media. Despite its significant impact, research is needed to evaluate the accuracy of the application of digital marketing in campus promotion. This study aims to analyze the influence of social media on prospective students' decision to enroll at ITB STIKOM Bali. Data was collected through a survey using a Likert Scale, with a total of 365 respondents. This research examines the influence of social media on marketing promotion at ITB STIKOM Bali. By analyzing respondents' responses, it was found that social media plays an important role in enrollment decisions, 81.09% of respondents often access social media to find information about ITB STIKOM Bali. Information about enrollment, campus activities, and testimonials delivered through social media proved to significantly influence prospective students' decisions. Social media is not only the main source of information but also builds trust and closeness between prospective students and ITB STIKOM Bali, making it an effective tool in attracting new applicants.